2007
DOI: 10.1002/jmor.10587
|View full text |Cite
|
Sign up to set email alerts
|

Bone modeling response to voluntary exercise in the hindlimb of mice

Abstract: The functional adaptation of juvenile mammalian limb bone to mechanical loading is necessary to maintain bone strength. Diaphyseal size and shape are modified during growth through the process of bone modeling. Although bone modeling is a well-documented response to increased mechanical stress on growing diaphyseal bone, the effect of proximodistal location on bone modeling remains unclear. Distal limb elements in cursorial mammals are longer and thinner, most likely to conserve energy during locomotion becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…[1][2][3][4] Due to the lack of bone mechanical loadings, reduced osteoid and mineralizing surfaces and decreased bone formation rate have been reported in space flight experiments, 5 and a similar effect of bone mass loss has been reported in scuba divers. 6 Physical training increases the cancellous bone and osteoinductive activity due to an increase of bone morphogenic proteins (BMPs), which decreases bone resorption and increases bone formation.…”
Section: Introductionmentioning
confidence: 73%
“…[1][2][3][4] Due to the lack of bone mechanical loadings, reduced osteoid and mineralizing surfaces and decreased bone formation rate have been reported in space flight experiments, 5 and a similar effect of bone mass loss has been reported in scuba divers. 6 Physical training increases the cancellous bone and osteoinductive activity due to an increase of bone morphogenic proteins (BMPs), which decreases bone resorption and increases bone formation.…”
Section: Introductionmentioning
confidence: 73%
“…The smaller outer bone size in B6‐exercise femora was opposite to expectations that exercise should be associated with an anabolic response,23 which motivated the replication of the study with five additional mice per group and strain. The only other known voluntary cage‐wheel running study reported in growing B6 female mice femora showed more than a doubling of periosteal area following 4 weeks of running 24. However, these mice had access to the cage wheel between 7 and 11 weeks of age.…”
Section: Discussionmentioning
confidence: 95%
“…The early ontogeny aspect of the study is important to highlight because of varied outcomes in the literature. Results range from reduced limb length with exercise (Kiiskinen, 1977;Li et al, 1991;Bourrin et al, 1994;Reich et al, 2005), to no effect (Nyska et al, 1995;Niehoff et al, 2004;Fritton et al, 2005;Hamrick et al, 2006), to increased limb length with exercise (Beyer, 1896;Adams, 1938;Buskirk et al, 1956;Tomljenovic Borer and Kuhns, 1977;Swissa-Sivan et al, 1989;Losos et al, 2001;Iwamoto et al, 2004;Plochocki et al, 2008;Serrat et al, 2010). Although nutrition, trauma, pathology, sex, severity, and duration of exercise are all potential factors that might explain some of the discrepancies among these studies (particularly the reduced limb growth) (Rogol et al, 2000;Forwood, 2008), much of the remaining variation could be explained by simply examining the age of the subjects.…”
Section: Examples Of a Critical Age Period In Exercise Studiesmentioning
confidence: 99%